L’Animation - Dionne, Pierre (Relations industrielles / Industrial Relations, 1968)
This article reviews "L’Animation" from the Cahiers de l’I.C.E.A.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z